REFLEKSI PEMIKIRAN ARISTOTELES SEBAGAI LANDASAN EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Adet Tamula Anugrah (An-Nahdlah: Jurnal Pendidikan Islam, 2021)
Abstract: The problem of education, especially in Islamic Religious Education Learning is very complex. Among these problems are three things that greatly affect the sustainability of the learning process, namely learning methods, teacher quality, and student character. Aristotle as a philosopher and a figure of learning theory has logical and systematic thinking as a foundation for the evaluation of Islamic Religious Education learning. So this research aims to synthesize Aristotle's thoughts and the learning of Islamic Religious Education as one of the foundations of learning evaluation. This research uses library research methods. The results of this study show that Aristotle's thoughts can be used as criticism and evaluation materials, especially regarding learning methods, teacher quality, and how to overcome students who have bad attitudes.